THE EFFECT OF BLOCKED VERSUS RANDOM TRAINING SCHEDULES ON BOCCIA SKILLS PERFORMANCE IN EXPERIENCED ATHLETES WITH CEREBRAL PALSY - Morriss, Luke; Wittmannová, Julie (European Journal of Adapted Physical Activity, 2010)
Efficiently maximising sporting performances through structuring of training sessions has become a very important focus over the past twenty years. Very little study directly related to boccia exists for athletes with cerebral palsy (CP) and consequently information on performance measures is scarce. The aim of study was to measure the effect of blocked versus random training schedules on boccia skills performance. Fourteen experienced national-level athletes with CP (M = 23.6 years) participated in this study. Athletes were divided in two intervention groups and followed prescribed blocked (n = seven athletes) and random (n = seven athletes) training schedules for 10 weeks. Data collection included pre- and post-tests original testing procedures. Two paired-samples Wilcoxon Signed Rank tests and a Mann-Whitney U test only generated statistically significant evidence to support blocked training (z = 2.29, p = 0.02, CI.90 = 9.50, 22.50). Despite this, findings and individual cases of improvements plus athletes and coaches remarks indicated a practical significance towards blocked training schedules over random training schedules in terms of improving boccia skills performance. Greater gains across all three boccia skills measured and in total mean difference between pre- and post-test were shown in favour of athletes following blocked training schedules.
Keywords: Cerebral palsy (CP); boccia; motor skills; performance; blocked and random training schedules